A flow-through UV/electro-chlorine process for cost-effective and multifunctional purification of marine aquaculture wastewater. Issue 2 (April 2022) - Lang, Zhicheng; Song, Xiangru; Song, Ge; Han, Lujie; Zhang, Qizhan; Zhou, Minghua
Abstract: This study validated the feasibility of the simultaneous removal of antibiotics such as sulfamethazine and other pollutants including ammonia nitrogen, nitrate nitrogen and phosphorus, as well as disinfection in marine aquaculture wastewater by using a flow-through ultraviolet/electro-chlorine (EO+UV) process, comparing the removal performance and energy consumption with that by separate EO and UV process. Due to the co-action of multiple radicals and free chlorine, the removal of sulfamethazine and ammonia nitrogen by using EO+UV process was much higher than that by using EO and UV. This process could achieve complete inactivation of bacteria and removal of sulfamethazine under optimal conditions of 10 mA (1.4 mA/cm 2 ), flow rate 15 mL/min and pH 8.0. It also exhibited an effective removal of other antibiotics (norfloxacin, chloramphenicol and cephalexin). During treatment, 5.0–87.0 mg/L free chlorine was generated by EO process at current of 10–50 mA (1.4–7.1 mA/cm 2 ), and it was further converted into a variety of radicals under UV irradiation such as hydroxyl (4.95–9.45 μmol/L) and chlorine radical, which greatly improved the performance and reduced the energy consumption to only 19.0 kWh/kg, far lower than other processes. This flow-through EO+UV process had great practical application prospects for the comprehensive removal of multiple pollutants especially antibiotics and sterilization from marine aquaculture wastewater. Graphical Abstract: ga1 Highlights: A new flow-through EO+UV was efficient for treatment of marine aquaculture wastewater. This process was feasible to remove antibiotics, NH4 + -N, P and disinfection simultaneously. Hydroxyl and chlorine radicals played the major role in the treatment as well as active chlorine. The energy consumption was 19 kWh/kg, much lower than other oxidative processes. The EO+UV process was promising and safe with low production of disinfection by-products.